Implementation Of Knowledge Management Among Malaysian ICT Companies: An Empirical Study Of Suceess Factors And Organisational Performance - Chong , Siong Choy (2005)
Knowledge management is a systematic management of organisational knowledge, which involves the process of creating, storing, gathering, organising and diffusing, use, exploitation and assessment of knowledge for creating business value and generating a competitive advantage. Therefore, the objective of this study is to (1) to identify the overall perception of knowledge management; (2) to develop valid measures that are associated with the degree of importance and degree of implementation of knowledge management and organisational performance; (3) to analyse the differences between perceived importance of knowledge management factors and implementation of the factors; (4) to analyse the association between knowledge management factors and organisational performance; and (5) to analyse the interaction between organisational demographic characteristics and knowledge management factors and organisational performance.